SARS-CoV-2 spike antibody concentration in gamma globulin products from high-prevalence COVID-19 countries are transmitted to X-linked agammaglobulinemia patients - Raphael, Allon; Shamriz, Oded; Tvito, Ariella; Magen, Sophie; Goldberg, Shmuel; Megged, Orli; Lev, Atar; Simon, Amos J.; Tal, Yuval; Somech, Raz; Eisenberg, Rachel; Toker, Ori (Frontiers in Immunology, 2023)
Purpose: Patients with X-linked agammaglobulinemia (XLA) are characterized by humoral impairment and are routinely treated with immunoglobulin replacement therapy (IGRT). In this study, we aimed to investigate the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies in intravenous immunoglobulin (IVIG) preparations harvested globally and evaluate the transfer of SARS-CoV-2 antibodies to the XLA patient. Methods: A single-center, prospective cohort study was conducted in the period of November 2020 to November 2022. Clinical and laboratory data, specifically, SARS-CoV-2 spike IgG levels from the serum of 115 IVIG preparations given to 5 XLA patient were collected. Concurrently, SARS-CoV-2 spike IgG levels from the serum of the 5 XLA was collected monthly. Results: Five XLA patients were evaluated within the study period. All were treated monthly with commercial IVIG preparations. A total of 115 IVIG treatments were given over the study period. The origin country and the date of IVIG harvesting was obtained for 111 (96%) of the treatments. Fifty-four IVIG preparations (49%) were harvested during the COVID-19 pandemic of which 76% were positive (>50AU/mL) for SARS-CoV-2 spike antibodies which were subsequently transmitted to the XLA patients in an approximate 10-fold reduction. SARS-CoV2 spike IgG was first detected in IVIG batches that completed their harvest date by September 2021. Positive products were harvested from origin countries with a documented prevalence over 2,000 per 100,000 population. Conclusion: As the prevalence of COVID-19 infections rises, detection of SARS-CoV-2 spike IgG in commercial IVIG products increases and is then transmitted to the patient. Future studies are needed to investigate the neutralizing capabilities of SARS-CoV-2 IgG and whether titer levels in IVIG remain consistent as the incidence of infection and vaccination rates in the population changes.